Representações sociais de universitários sobre a influência da relação professor e estudante na motivação da aprendizagem - Santos, Charlene Carneiro Quinto dos (2024)
Learning motivation has aroused the interest of several researchers in recent years (Bzuneck; Boruchovitch, 2016). In this context, the teacher-student relationship emerges as one of the factors that can favor or hinder learning motivation (Schwartz, 2019). As there are still few studies on this subject, investigating it from the point of view of higher education and in the light of the Theory of Social Representations, we conducted this study in search of the following question: How does the teacher-student relationship influence the learning motivation of undergraduates on the Vernacular Languages course at UEFS? Therefore, this research sought to understand and analyze the representations of students on the Vernacular Literature course at UEFS about the influence of the teacher-student relationship on learning motivation. To this end, we sought support from contemporary theories on learning motivation (Pintrich; Schunk, 2006), the Theory of Social Representations (Moscovici, 1961), and the Educational Relationship (Postic, 1984). With a qualitative approach (Minayo, 2013), this research is part of a larger study developed by the Center for Studies and Research on University Pedagogy (NEPPU/UEFS). To produce the data, we used a semi-structured interview with metaphor induction, carried out with ten students on the Vernacular Languages course at UEFS. To analyze the data produced in the interview, we used Bardin's Content Analysis (1977). There was a consensus in the representations analyzed that the teacher-student relationship has a substantial influence on learning motivation, in a way that can benefit or harm it. For undergraduates, learning motivation is associated with more self-determined forms of motivation, and this tends to improve when the teacher-student relationship is characterized by affection, acceptance, dialogue, listening, empathy, interest in student learning and teacher professionalism. Meanwhile, demotivation was represented as an obstacle that threatens learning, and this condition intensifies when the teacher-student relationship is marked by authoritarianism, a lack of empathy and acceptance, a lack of interest in student learning and the teacher's lack of professional commitment. In addition, we identified in the undergraduates' representations that teaching is a complex profession, and this complexity can be mitigated through teacher training that takes into account the teacher-student relationship and its intersections with learning motivation, which will enable changes in the teacher-student relationship with a view to enhancing learning motivation. In addition, it was observed that the teacher-student relationship in teacher training courses has a formative character, in that this relationship can serve as a model for the practice of future primary school teachers.